2018
DOI: 10.3892/etm.2018.5894
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, culture and induced differentiation of rabbit mesenchymal stem cells into osteoblasts

Abstract: Mesenchymal stem cells (MSCs) may be easily isolated from the bone marrow, and possess multi-lineage differentiation potential and various therapeutic applications. The differentiation of MSCs into osteoblasts is a complex process that is regulated by multiple internal and external factors. In the present study, the differentiation of MSCs isolated from rabbit bone marrow into osteoblasts using different osteoblast inductive media in the presence of dexamethasone, bone morphogenetic protein 2 (BMP-2), 1,25-dih… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Dexamethasone supplementation up‐regulated BMP2 expression in Jagged1‐treated condition similar to those cultured in osteogenic induction medium. Correspondingly, previous report demonstrated that dexamethasone induced BMP2 mRNA and protein expression in mesenchymal stem cells (Liu et al, 2018a, 2018b). Dexamethasone interacted with BMP2 then regulated osteogenic differentiation in human MSC (Jager et al, 2008).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Dexamethasone supplementation up‐regulated BMP2 expression in Jagged1‐treated condition similar to those cultured in osteogenic induction medium. Correspondingly, previous report demonstrated that dexamethasone induced BMP2 mRNA and protein expression in mesenchymal stem cells (Liu et al, 2018a, 2018b). Dexamethasone interacted with BMP2 then regulated osteogenic differentiation in human MSC (Jager et al, 2008).…”
Section: Discussionsupporting
confidence: 54%
“…SB431542 treatment (as low as 0.1 μmol L −1 ) significantly increased mineralization in human gingival mesenchymal stem cells and the addition of SB431542 at 1 μmol L −1 markedly increased osteogenic differentiation both in vitro and in vivo (Shi et al, 2019). It has also been shown that the optimal dose for SB505124 in osteogenic induction of bone marrow derived from Sh3bp2 KI/KI mice was 100–250 nmol L −1 (Liu et al, 2018a, 2018b). Further, SB505124 (10–1000 nmol L −1 ) inhibited chorion membrane extracts‐induced calcium deposition under osteogenic induction of MG‐63 cells (Go et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Being expressed at the early to middle stages of osteo-differentiation, ALP and COL were up-regulated during the first 2 weeks of cell culture without further increase of mRNA expression after day 21 [ 59 ]. On the other hand, the late expression of OCN could be confirmed from the continued increase of mRNA expression up to 28 days [ 60 ]. The scaffold-dependent analysis on gene expression further endorses the effect of PRP/BCP in controlling the expression of various osteogenic markers.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, when osteoblasts are cultured in vitro, they will cause the deposition of calcium salts, thereby forming calci ed nodules. The more calcium salts are deposited, the better the osteogenic differentiation [24].…”
Section: Discussionmentioning
confidence: 99%